Is It All About the Data? How Extruded Polystyrene Escaped Single-Use Plastic Directive Market Restrictions - Troya, María Del Camino; Power, Orla-Peach; Kopke, Kathrin (Frontiers in Marine Science, 2022)
The Single-Use Plastics Directive (EU) 72/2019/904 is the main legislation governing plastic pollution, inclusive of marine plastic pollution in the European Union (EU). The Directive has issued market restrictions on several single-use plastic products which contribute to marine plastic pollution, including foamed polystyrene products made of expanded polystyrene (EPS). However, extruded polystyrene (XPS) which is commonly used in the same single-use plastics products as EPS has been omitted from the market placement restrictions within the scope of the Directive. This has subsequently compromised the Single-Use Plastics Directive’s effectiveness for reducing marine plastic pollution and hinders the efforts of related EU instruments such as the Marine Strategy Framework Directive, Descriptor 10 toward achieving Good Environmental Status across the marine environment in the EU. This paper provides some background on EPS and XPS, and discusses plastic pollution policy making in the EU, while further addressing the role of quantitative data in the European Joint Research Centre’s Technical Report on Top Marine Beach Litter Items in the EU for the formulation of policy regulating foamed polystyrene derived marine plastic pollution. We also provide an overview of how the communication gaps in the polymer science nomenclature for polystyrene may have contributed to the development of misnomers for extruded and EPS, consequently compromising necessary data gathering efforts. Our perspective hopes to incite conversations on communication gaps between scientists and policy makers and emphasise the need for gathering quantitative disaggregated data on the foamed polystyrene market to inform European plastic pollution legislation adequately.